Family-based Early Intervention of Verbal Expressive Language Skills for children with Autism Spectrum Disorder (ASD) - Justitie, Geovanka Bellausnova Van; Aprilia, Imas Diana (Department of Special Education, 2024)
Cases of children experiencing speech impediments occur in children with Autism Spectrum Disorder (ASD) because most of them have difficulty in mastering verbal language. The role of the family to reduce the gap is needed so that the child's development can occur optimally. Using the Mand model is expected to help reduce gaps and optimize verbal expressive language development through family-based early intervention. First, a child profile and family profile are developed into a program to address children's verbal expressive language needs and family skill needs. The form of intervention carried out includes the implementation of the program from the interventionist to the family and the implementation of the intervention from the family to the child. The results of the intervention program indicate that the mand model is effective. Children's verbal expressive language skills increase as seen from the acquisition of new vocabulary that children can say. This model is also effective for families because it is natural and easy to follow.